New Year's Day - Schuh, Mari C., 1975- (Mankato, Minn. : Pebble Books, 2003)
Simple text and photographs describe the history of New Year's Day and the many ways in which it is celebrated.
Includes bibliographical references (p. 23) and index.
2.6
K-3.
K-3
Keywords: Holidays -- Juvenile literature; New Year -- Juvenile literature; Holidays; New Year; Holidays; New Year